Il turpiloquio nella comunicazione pubblica russa contemporanea (Altre Modernità, 2020)
The paper shall discuss the different evaluations to which the Russian foul language has been submitted since the fall of the Soviet Union, moving throughout three decades from a state of marginality to institutional legitimization and again to marginality while maintaining a high level of popularity and creative force. Firstly, a theoretical frame will be given, outlining the main features and function of foul language. Secondly, some examples of swearing by political elites will be shown, which initially fostered the massification of vulgar language, facilitated also by the rapid spread of the Internet. Thirdly and finally, an analysis of the legislative interventions carried out since the early 2000s in order to achieve a restriction of the norm will be provided, trying to frame the current dialectic between the Russian speakers' community and the government's linguistic policy in the broader framework of the political status quo of the “power vertical”.